2024
DOI: 10.1590/1519-6984.255493
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of tambaqui (Colossoma macropomum) fed diets supplemented with silage from fish and vegetables residues

Abstract: The demand for products to replace high-cost raw materials, such oil and fish meal, in the manufacture of feed for use in aquaculture, while also guaranteeing the nutritional quality of the diets, is increasing. Silage produced with fish and vegetables residues is a low-cost and efficient protein source. The objective of the present study was to evaluate the physiological and biochemical responses of tambaqui fingerlings fed four different levels of silage included in commercial feed with 28% crude protein, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
2
3
0
1
Order By: Relevance
“…Similar to the present ndings, sh processing waste silages also promoted the growth of tambaqui juveniles, not being statistically different from diets formulated with conventional ingredients (Costa et al 2022). The weight gain values presented by the tambaqui in this study are within range from the results observed by Costa et al (2022) for sh under experimental conditions fed for 13 weeks.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the present ndings, sh processing waste silages also promoted the growth of tambaqui juveniles, not being statistically different from diets formulated with conventional ingredients (Costa et al 2022). The weight gain values presented by the tambaqui in this study are within range from the results observed by Costa et al (2022) for sh under experimental conditions fed for 13 weeks.…”
Section: Discussionsupporting
confidence: 87%
“…Além disso, os tratamentos com os níveis mais altos de EOZO reduziram os níveis de albumina plasmática, alanina aminotransferase e aspartato aminotransferase e aumentaram os níveis de leucócitos, hemoglobina e trombócitos, glicemia e colesterol plasmático (Chung et al O grupo controle apresentou altas vilosidades, espessura epitelial, e parece que a adição de 0,5 ml de EOZO kg diet −1 pode melhorar alguns parâmetros fisiológicos (leucócitos, hemoglobina e trombócitos e níveis plasmáticos de ALT e AST) sem causar danos ao fígado ou afetar negativamente as vilosidades intestinais de juvenis de tambaqui. Costa et al (2022) avaliaram as respostas fisiológicas e bioquímicas de alevinos de tambaqui (31,15 ± 3,65 g) alimentados com quatro diferentes níveis de silagem incluída em ração comercial com 28% de proteína bruta, em dois períodos: 45 e 90 dias. A silagem foi incluída na ração moída em quatro níveis: 0% (controle, sem silagem), 5% (25 g de silagem e 500 g de ração moída), 10% (50 g de silagem e 500 g de ração moída) e 20% (100 g de silagem e 500 g de ração moída).…”
Section: 25%unclassified
“…Given the assumptions presented above, it is reasonable to consider the use and processing of residues from fish processing, such as fertilizers for agriculture and gardening, 13 silage production 14,15 or hydrolysates, 16 reused alternatives in animal nutrition and agrochemicals, as well as other benefits to the consumer market such as ecological leather from fish skin in the manufacture of shoes, bags, carpets and other leather products. 17 According to Cavali et al 7 and Vilhena et al, 18 the above-mentioned co-products provide interesting advantages for the fish farming sector, as they are a low-cost raw material simultaneously with high productivity, and are also capable of minimizing the problem of waste from fish processing.…”
Section: Introductionmentioning
confidence: 99%